Banalitas Informasi Jurnalisme Infotainment dan Dampaknya terhadap Penonton - Tri Hastuti Nur R; Fajar Junaedi (Jurnal Komunikasi, 2010)
This article is based on a research of information banality in television infotainment programs and the effects to the audience. The research uses the ethnography of communication method at the level of decoding and encoding process. It results that in infotainment production process, TV station often disregards the journalism ethic principles. This statement is proved by -for example - many cases of some celebrities sue the infotainment crew because the celebs feel suffered by infotainment news. The infotainment news packaging in infotainment program also shows a phenomenon called “market-driven journalism”, which breaks the “cover both side" principle. At the decoding process, public in three locations that's been researched show different inclination. Some are critical and don't let their children watch infotainment, while the others watch infotainment intensively and even allow their children watch it too. Despite, they do know and aware that the infotainment can be harmful to their children.